2010
DOI: 10.1038/gene.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene signature revealed in white blood cells, CD4+ and CD8+ T cells in (NZBx NZW) F1 lupus mice after tolerization with anti-DNA Ig peptide

Abstract: Tolerizing mice polygenically predisposed to lupus-like disease (NZB/NZW F1 females) with a peptide mimicking anti-DNA IgG sequences containing MHC class I and class II T cell determinants (pConsensus, pCons) results in protection from full-blown disease attributable in part to the induction of CD4 þ CD25 þ Foxp3 þ and CD8 þ Foxp3 þ regulatory T cells. We compared 45 000 murine genes in total white blood cells (WBC), CD4 þ T cells, and CD8 þ T cells from splenocytes of (NZBxNZW) F1 lupus-prone mice tolerized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…Semplicini et al reported that reduction of RGS2 signaling increases Ca 2+ mobilization and ERK1/2 activation in response to GPCR stimulation [84]. We found that multiple RGS proteins are downregulated in tolerized CD8 + Ti cells [58]. …”
Section: Cellular Molecular and Functional Basis For Gene Selectmentioning
confidence: 59%
See 4 more Smart Citations
“…Semplicini et al reported that reduction of RGS2 signaling increases Ca 2+ mobilization and ERK1/2 activation in response to GPCR stimulation [84]. We found that multiple RGS proteins are downregulated in tolerized CD8 + Ti cells [58]. …”
Section: Cellular Molecular and Functional Basis For Gene Selectmentioning
confidence: 59%
“…A recent study identifies the major role of p53 in the increased formation of exosomes, a non-classical protein secretion pathway, by upregulated expression of the target gene TSAP6 [65, 69]. We detected increased expression of p53 in CD8 + Ti [58]. Conceivably, p53 may play a novel role in support of CD8+Ti-mediated tolerance by promoting the exosome-mediated delivery of TGFβ or other key growth factors.…”
Section: Cellular Molecular and Functional Basis For Gene Selectmentioning
confidence: 80%
See 3 more Smart Citations